Recent Advances in Insect Rearing Methodology to Promote Scientific Research and Mass Production - Man P. Huynh (MDPI AG, 2021)
The benefits obtained from our ability to produce insects have encompassed a wide array of applications, from the early stages of examining different species, to the present day of mass production for multiple purposes [...]